Follow the money : the impact of the illicit financial flows home and abroad : a common european-african perspective - Razvan Hoinaru (Revista română de economie, 2017)
The recently documented impact of Illicit Financial Flows (IFFs) challenged global organisations to propose solutions and sign agreements. Multilateral conventions and international cooperation programmes were placed on agendas by global organisations like OECD, IMF, G20, World Bank. Combatting IFF combines the purposes of addressing vulnerabilities, protecting people and resources, bringing financial stability, economic development, human development and diminishing crime. IFF is primarily of a political nature, however it happens because of money laundering, trade mispricing, bad financial reporting, tax avoidance, shell companies, etc. As well as being an African issue, IFF is a European one as well. Regional bodies like the European Parliament and African Union are specifically addressing the effecting issues further. In the process of legislation making, under the umbrella of the ACP-EU Parliamentary Partnership, is the Stolojan-Kaba report on the Impact of Illicit Financial Flows on Development Finance. This piece of legislation is of particular importance as it shows common interest and two-headed leadership from both the EU and African side. The purpose of this article is to analyse the policy coherence on the subject matter around the world and how efforts done separately, home and abroad, are put together. A second purpose of the article is to follow the money by presenting the accountability dimension of accounting and discover who is paying the price.
2665773-9; 2344-4657; Revista română de economie; 717197875